Orthodontic treatment planning for impacted maxillary canines using conventional records versus 3D CBCT - Ali Alqerban; Guy Willems; Christien Bernaerts; Jan Vangastel; Constantinus Politis; Reinhilde Jacobs (2014)
The aim of this study was to compare the orthodontic treatment planning for impacted maxillary canines based on conventional orthodontic treatment records versus three-dimensional (3D) information taken from single cone beam computed tomography (CBCT) scans. This study consisted of 40 individuals with impacted maxillary canines. Patients were identified from among those referred for orthodontic treatment (26 females, 14 males) with a mean age of 12.5 years (± SD 3). In total, 64 impacted canines were identified, justifying the need for CBCT scans by the treating orthodontist. Two sets of information were obtained. The first set consisted of conventional planning records [two-dimensional (2D) panoramic, 2D lateral cephalograms, and dental casts] and the second set of 3D volumetric images obtained from a single CBCT scan (3D panoramic, 3D lateral cephalograms, 3D virtual study model). For both sets, intra- and extraoral images were included. The radiographic diagnostic features, treatment planning, orthodontists' opinions, and case classifications of both sets were produced and subsequently analysed by four orthodontists. There was no statistically significant difference in treatment planning between the use of both sets, in terms of either orthopaedic growth modification or orthodontic compensation. Also, anticipated complications during treatment and expected treatment duration did not differ significantly. Orthodontists found the conventional set to be insufficient for treatment planning in 22.5 per cent and requested additional radiographs needed in 63 per cent of cases, compared with 1.3 and 0.5 per cent, respectively (P < 0.001). The observers' confidence level was higher for therapy based on the 3D set compared with the conventional set (96.3 per cent versus 61.9 per cent, P < 0.001). There was no statistically significant difference in treatment planning between the use of conventional and CBCT sets. CBCT images have been shown to offer useful orthodontic treatment planning information similar to that of conventional planning with a high confidence level.